ANALISIS TEKNIKAL SAHAM DENGAN INDIKATOR STOCHASTIC RSI (RELATIVE STRENGTH INDEX) - , MUHAMMAD RIO NUGRAHA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Technical analysis of stock is an analytical method which tests the previous price in order to predict the future of the price movenment. The technical analysis of stock is good to help traders in predicting the right time to get in and out of the stock market. There are some indicators used in technical analysis, one of them is Stochastic RSI (Relative Strength Index). Stochastic RSI (Relative Strength Index) is an indicator that the calculation analysis similar to the Stochastic Oscillator but for the data of choices and usually replaced with the highest highs and the lowest of data from RSI (Relative strenth Index) which is predicted to produce more accurate predictions than other indicators, where the this thesis will use the 25 period will be compared to a more precise prediction of the signal between the Stochastic oscillator and Stochastic RSI.